THE EFFECT OF GOOD CORPORATE GOVERNANCE ON THE EFFICIENCY OF ISLAMIC BANKS FROM 2012 TO 2016 WITH SOCIAL PERFORMANCE AS AN INTERVENING VARIABLE - Ghofur, Abdul; Sukmaningrum, Puji Sucia (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2018)
This study aims to determine the effect of Good Corporate Governance and social performance on efficiency in Bank Syariah Period 2012-2016. The sample in this study used a purposive sampling method of Islamic Commercial Banks (BUS) in Indonesia, from 13 BUS took 6 BUS that met the sample criteria to be tested. Furthermore, this research uses path analysis, while the research approach used is quantitative approach using analysis technique PLS (Partial Least Square). In this research, there are three latent variables namely Good Corporate Governance as an exogenous or independent variable, social performance as endogen intervention variable, and efficiency as an endogen variable. The indicators used to reflect the Good Corporate Governance Variables are the Board of Commissioners (DK), the Composition of Independent Commissioners (KDKI), the Sharia Supervisory Board (DPS), the Frequency of Sharia Supervisory Board Meetings (FRDPS), and the Frequency of Audit Committee Meetings (FRKA). The indicators used to reflect social performance are financing Mudharabah-Musyarakah, Zakat, and Qard.. Furthermore, the efficiency indicator is reflected by the ratio of BOPO (Operational Cost to Operating Income). The results of this study indicate that GCG has a significant positive effect on efficiency, GCG has a significant positive effect on social performance, social performance has a significant negative effect on efficiency, GCG has a significant negative effect on efficiency through social performance.          Keywords: Good Corporate Governance, Social Performance, Efficiency, Islamic Banks